1995
DOI: 10.1159/000276723
|View full text |Cite
|
Sign up to set email alerts
|

Subepithelial Fiber Components of the Round Window Membrane of the Guinea Pig: An Ultrastructural and Immunohistochemical Study

Abstract: Subepithelial fiber components of the round window membrane (RWM) of the guinea pig were studied by the following methods: transmission electron microscopy (TEM), scanning electron microscopy (SEM) with NaOH treatment, high-voltage electron microscopy (HVEM) and immunohistochemical staining. SEM observation revealed intersecting collagen fibers and a vascular network in the middle layer. TEM observation showed that at the attachment region to the bone fïbroblasts, collagen fibers and elastic fibers were interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…36 In a laboratory setting, they are usually used to separate cells, or more specifically epithelial cells. As the RWM contains mainly type I collagen, 37 we hypothesized that type I collagenase may be more effective in digesting the RWM. However, we have found that at appropriate concentrations, both type I and II collagenase are equally effective.…”
Section: Discussionmentioning
confidence: 99%
“…36 In a laboratory setting, they are usually used to separate cells, or more specifically epithelial cells. As the RWM contains mainly type I collagen, 37 we hypothesized that type I collagenase may be more effective in digesting the RWM. However, we have found that at appropriate concentrations, both type I and II collagenase are equally effective.…”
Section: Discussionmentioning
confidence: 99%